2021
DOI: 10.3390/ijerph182111228
|View full text |Cite
|
Sign up to set email alerts
|

A One-Year Longitudinal Study: Changes in Depression and Anxiety in Frontline Emergency Department Healthcare Workers in the COVID-19 Pandemic

Abstract: Frontline healthcare workers (HCWs) fighting COVID-19 have been associated with depression and anxiety, but there is limited data to illustrate these changes over time. We aim to quantify the changes in depression and anxiety amongst Emergency Department (ED) HCWs over one year and examine the factors associated with these changes. In this longitudinal single-centre study in Singapore, all ED HCWs were prospectively recruited face-to-face. Paper-based surveys were administered in June 2020 and June 2021. Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 45 publications
11
44
1
Order By: Relevance
“…However, until now, limited published studies were available evaluating the changes in the mental health of HCPs during the course of the pandemic and more specifically comparing the differences over the different waves. Similar to our findings, other studies [ 44 ] also reported higher odds of psychological distress, such as depression and anxiety, among those HCPs who were involved with the treatment of patients suffering from COVID19. Additionally, a longitudinal study that was carried out in Japan and evaluated four waves of the pandemic showed that even when the cases of COVID 19 were low, HCPs continuously experienced high psychological distress [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, until now, limited published studies were available evaluating the changes in the mental health of HCPs during the course of the pandemic and more specifically comparing the differences over the different waves. Similar to our findings, other studies [ 44 ] also reported higher odds of psychological distress, such as depression and anxiety, among those HCPs who were involved with the treatment of patients suffering from COVID19. Additionally, a longitudinal study that was carried out in Japan and evaluated four waves of the pandemic showed that even when the cases of COVID 19 were low, HCPs continuously experienced high psychological distress [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…The existing literature reported that the prevalence of psychological symptoms in HCPs during the COVID-19 pandemic was higher than in the previous epidemics [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. We found that during the second wave, the participants felt angrier and lonelier compared to the first, with 22% presenting clinically significant anger and 54.3% indicating significant loneliness.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…AcHCPs (working in intensive care, anaesthesia, and emergency medicine) were the vast majority of front-line HCPs during the COVID-19 pandemic. AcHCPs faced personal protective equipment, medications, and ventilator shortages and needed to care daily for severely ill or dying patients ( Greenberg et al, 2015 ; Magnavita et al, 2020b ; Th’ng et al, 2021 ; Tsan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with 2020, there was an increase in burnout, poorer self‐rated health and reduced job dedication among the nurses 2021. Similar longitudinal analysis studies, albeit conducted among doctors in the United Kingdom and Ireland (Roberts et al, 2021 ) and Singapore (Th'ng et al, 2021 ), reported an increase in the prevalence of psychological distress (44.7%) and trauma (23.7%) (Roberts et al, 2021 ) during the COVID‐19 pandemic. Similarly, a study conducted in an emergency department in Singapore reported a significant worsening of the depression level reported among the doctors (Th'ng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 68%